2010
DOI: 10.1002/j.1551-8833.2010.tb11339.x
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic activity of US drinking waters: A relative exposure comparison

Abstract: This study demonstrates a relative exposure to estrogenic activity and other trace contaminants in drinking water compared with food, beverage, and air exposure. Drinking water for nearly 28 million people in 17 US cities plus 40 food and beverage items was screened for 51 trace contaminants, including suspected endocrine disrupting chemicals (EDCs), pharmaceuticals, personal care products, pesticides, phytoestrogens, and total in vitro estrogenic activity. Only three drinking water samples exhibited measurabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 58 publications
2
15
0
1
Order By: Relevance
“…Klinge et al (2003) detected a maximum of 84 ng E 2 Eq/L (308.3 pM E 2 Eq/L) in red wine, and Promberger et al (2001) reported a range from 23 to 41 ng E 2 Eq/L (84-150 pM E 2 Eq/L) in beer. These results were confirmed by Takamura-Enya et al (2003) and Stanford et al (2010), who reported a maximum activity of 140 ng E 2 Eq/L (513.9 pM E 2 Eq/L) in beer. Hartmann et al (1998) suggested that dairy products are the main source of estrogens, calculating a total daily intake of 80-100 ng estrogens per day for adults.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…Klinge et al (2003) detected a maximum of 84 ng E 2 Eq/L (308.3 pM E 2 Eq/L) in red wine, and Promberger et al (2001) reported a range from 23 to 41 ng E 2 Eq/L (84-150 pM E 2 Eq/L) in beer. These results were confirmed by Takamura-Enya et al (2003) and Stanford et al (2010), who reported a maximum activity of 140 ng E 2 Eq/L (513.9 pM E 2 Eq/L) in beer. Hartmann et al (1998) suggested that dairy products are the main source of estrogens, calculating a total daily intake of 80-100 ng estrogens per day for adults.…”
Section: Introductionsupporting
confidence: 93%
“…For example, our own group associated the estrogenic burden (range 5.44-720 nM E 2 Eq/L) in the liquor of vegetables packed in lacquer-coated cans with the presence of bisphenol-A (BPA) from epoxy resins (Brotons et al, 1995) and related the estrogenicity of baby food products (range 0.25-70.13 pM E 2 Eq/g) to the food packaging (Pandelova et al, 2011). In drinking waters, a maximum of 8.7 ng E 2 Eq/L (31.94 pM E 2 Eq/L) was detected in Brazil (Bergamasco et al, 2011) and a range of 0.19-0.72 ng E 2 Eq/L (0.7-2.64 pM E 2 Eq/L) in the USA (Stanford et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Applying the factor used by Thomson (Thomson et al, 2003), the EEQ plasma levels obtained would result in an estimate of 0.7-0.9 ng EEQ/L, a level that is not likely to be of health significance for the population, confirming the results of our previous study . However, it is also feasible that total daily intake of EDCs might exceed our estimate due to possible contributions from as-yetundetermined EDCs in foods and beverages (Guenter et al, 2002;Muncke et al, 2009;Stanford et al, 2010;Wagner et al, 2011) and from other environmental sources (Takamura-Enya et al, 2003). For example, Behr and colleagues conclude that pesticide residues exhibit only marginal impacts on the estrogenic activity in the diet.…”
Section: Discussionmentioning
confidence: 89%
“…A common chemical additive, bisphenol A (BPA; EEq ~ 0.0001), has two H-bond donor groups but non-optimal shape . Finally, phytoestrogens (EEq ~ 0.0007), which are plantderived chemicals present at high concentrations in many food products (NCEH 2005;Stanford, Snyder et al 2010), have a molecular core that is typically more polar than that of steroidal estrogens ).…”
Section: A Range Of Estrogen-like Chemicalsmentioning
confidence: 99%